Polymyositis concomitant with hepatitis B virus infection: Treatment challenges - Ginting, Andi R.; Tandiono, Vincent (Narra J, 2023)
Polymyositis is a chronic autoimmune disease that presents with symmetrical progressive proximal muscle weakness. The cause of this disease due to abnormal activation of macrophages that might be associated with systemic diseases such as other autoimmune diseases, malignancy or viral infections including hepatitis B virus. The aim of this case report was to highlight treatment challenges in a patient with polymyositis concomitant with hepatitis B. A 28-years-old man with history of completed hepatitis B treatment with negative viral load presented with symmetrical progressive weakness on both inferior proximal extremities. The patient complained of pain predominantly in both tights and calves. No dermatological manifestation was observed. Elevated muscle enzymes and liver function were observed. Along with the course of the disease, hepatitis B reactivation was discovered as hepatitis B virus DNA was re-detected. Treatment options of this patient (polymyositis concomitant with hepatitis B viral infection) remain challenging. The main treatment of polymyositis consists of high dose methylprednisolone and this immunosuppressant could worsen the hepatitis B virus infection. The patient was finally treated with combination of mycophenolic acid and methylprednisolone for polymyositis and entecavir for hepatitis B. After one month of treatment, the patient showed a clinical improvement. This case highlights that viral screening must be done prior to starting polymyositis treatment as it could concomitant with viral infections such as hepatitis B. Antiviral prophylaxis must be given 1–2 weeks before immunosuppression starts. Management for both polymyositis and hepatitis B is important with entecavir or tenofovir as the optimal agents against hepatitis B virus.